An ASP.NET web application for therapist - Chng, Drake Yao Guang (2015)
The Information Age today has radically reshaped the modern lifestyle. Computers, networks and telecommunications have immensely disorganise and re- invented some of society’s most crucial elements of how we communicate and socialise. The technology of today has moulded society to expect that every aspect of life will be quick, efficient, streamlined and available immediately on demand. The Healthcare Industry has seen an increase dependence on engineering technology with the past few decades having biomedical technologies being incorporated into hospitals and clinical environments. Such technologies include new techniques for imaging both structure and function of body organs, and information technology designed to handle large quantities of patient data in multiple modalities, safely and efficiently. The Medical Information System (MIS) is an example of where information technology is being leveraged to efficiently handle patients information and communications between medical professionals of a medical institution or facility. The Medical Information System aims to shift from a paper-based record environment to an Electronic Health Record (EHR) / Electronic Medical Record (EMR) environment and to connect medical professionals from various departments together through a unified platform that is beneficial for both the medical professionals and patients. This report aims to inform the reader about the functionalities and benefits of the Medical Information System. This report also provides technical information about the designs and implementations of various technologies used within the Medical Information System. The shortcomings of the current Medical Information Systems are also highlighted in this report, so as to share with readers who are developing on the next iterations of the Medical Information System.